Gratitude and sleep disturbance in primary care patients: the mediating roles of health self-efficacy, health behaviors, and psychological distress - Altier, Heather R.; Hirsch, Jameson K.; Weber, Annemarie; Kohls, Niko; Schelling, Jörg; Toussaint, Loren L.; Sirois, Fuschia M.; Offenbächer, Martin (Frontiers in Sleep, 2025)
IntroductionSleep disturbances are prevalent among primary care patients, and psychological dysfunction, including stress, anxiety, and depression, are robust contributors to poor sleep health. Yet, the presence of potential protective characteristics, such as health self-efficacy and engaging in adaptive health behaviors, may mitigate such outcomes. Gratitude (i.e., recognition and appreciation of experiences, relationships, and surroundings), a positive psychological cognitive-emotional characteristic, may serve as a catalyst of these beneficial downstream effects, given its association with improved health functioning and sleep.MethodsIn a sample of primary care patients (N = 869, M age = 53; 60.7% female) from 50 urban and 30 rural practices in Germany, health self-efficacy (i.e., belief in ability to perform necessary actions to manage health) and constructive health behaviors (i.e., actions taken to modify health positively), separately and together as parallel first-order mediators, and stress, anxiety, and depression, as parallel second-order mediators, were investigated as potential serial mediators of the association between gratitude and sleep disturbances. Participants completed self-report measures in person and online.ResultsSignificant serial mediation was observed across models, although effects varied. In the first model, gratitude was associated with greater health self-efficacy and, in turn, to less stress (a1d21b4 = −0.019, 95% CI [−0.039, −0.002], SE = 0.010), anxiety (a1d31b5 = −0.026, 95% CI [−0.045, −0.008], SE = 0.009), and depression (a1d41b6 = −0.020, 95% CI [−0.040, −0.003], SE = 0.009), and fewer consequent sleep disturbances. In the second model, health behaviors, and anxiety (a1d31b5 = −0.009, 95% CI [−0.019, −0.002], SE = 0.004) and depression (a1d41b6 = −0.007, 95% CI [−0.016, −0.001], SE = 0.004), were serial mediators, but health behaviors and stress were not. In a final combined model, serial mediation occurred on two pathways, health self-efficacy and anxiety (a1d41b6 = −0.026, 95% CI [−0.046, −0.009], SE = 0.009), and health self-efficacy and depression (a1d51b7 = −0.019, 95% CI [−0.037, −0.003], SE = 0.009), and a specific indirect effect was found for health behaviors (a2b4= −0.086, 95% CI [−0.140, −0.030], SE = 0.026), but not self-efficacy.DiscussionOverall, gratitude was associated with reduced sleep disturbances through positive health behavior engagement, and via the serial mediation effects of greater health self-efficacy and lower psychological distress. Clinical interventions that enhance gratitude (e.g., gratitude listing or diaries), self-efficacy (e.g., disease self-management programs), or health behavior engagement (e.g., weight management programs) may promote favorable downstream effects on psychological distress and sleep disturbances among primary care patients.